Neuropathology And Diagnosis Of Rabies In Domestic animals - Silamban S (Department of Pathology, College of Veterinary and Animal Sciences, 1996)
An investigation was made to study the epidemiology, clinical signs, pathologic lesions and diagnosis of rabies in domestic animals in the state of Kerala. Epidemiology of rabies for the last 12 year period from July 1983 to June 1995 was assessed from the post – mortem records maintained at the department of Pathology. Regional distribution, Prevalence in each species and year – wise occurrence were studied. Canine rabies was found preponderant. Rabies was recorded in wild animals also. Detailed clinical signs and gross pathological changes in the rabies positive cases were studied. One hundred and six rabies suspected carcasses of different species of animals were examined for the disease employing Sellers’ impression smear staining, histopathology, fluorescent antibody test (FA test) and immunoperoxidase test (IP test). Twenty – two of them were confirmed positive for rabies. Negribodies were demonstrated with Sellers’ staining and histopathological staining. Sellers’ staining was identified to be the simple and rapid staining method that could be employed in the field laboratories. In addition to H & E, Mann’s stain and Sellers’ stain were applied for staining histological sections. H & E was found to be satisfactory for routine staining. Histological changes in the brain (cerebrum, cerebellum and hippocampus), salivary gland (parotid and submaxillary) and trigeminal nerve of rabies positive animals were studied. The efficacy of the diagnostic techniques used for rabies diagnosis was compared. FA test confirmed maximum number of rabies positive cases. The results of the rabies diagnosis was cross – checked by Veterinary Diagnostic Laboratory, College of Veterinary Medicine, Oregon State University, USA.